Morphosyntactic changes induced by language contact based on the LangGener corpus of German-Polish bilingualism - Jorroch, Anna; Księżyk, Felicja; Prawdzic-Jankowska, Irena; Zielińska, Anna (Papers in Linguistics, 2025)
The aim of the article is to determine whether morphosyntactic changes induced by Polish-German/German-Polish language contact in the speech of bilingual individuals are generationally differentiated. The submitted text will thus attempt to answer the research question posed in the Polish-German project – Language across Generations: Contact Induced Change in Morphosyntax in German-Polish Bilingual Speech. The concept of generations adopted by the LangGener project takes into account geographical, historical and linguistic aspects. Generations are named after the country in which their representatives live (Generation Poland and Generation Germany). The oral corpus of Polish-German bilingualism LangGener is the source of data to answer this question. The article presents the concept of this corpus, as well as the principles of morphosyntactic annotation it follows. The proposed study presents morphosyntactic replications from German in Polish and the other way round. Quantitative comparison of the types of replications in both languages in both generations is also made.